Teoria e práxis da defesa da concorrência no Brasil. - Marina Moreira da Gama (2005)
The brazilian antitrust policy is built through the CADEs decisions. CADE is the national agency which effectively decides a requirement concerning concentration acts and anticompetitive conducts. To appraise the CADEs decisions, thus, is to appraise the antitrust policy in Brazil. This implies that is necessary to know if these decisions are cosistent with the antitrust theory. Then, the purpose of this dissertation is to verify the theoretical consistency of CADEs decisions towards the new brazilian antitrust statute: Law 8.884 of 6/11/1994, since this define the brazilian antitrust agencys practice.